Consciência política e participação dos sindicalistas em ações coletivas contra a privatização - Oliveira Neto, Joaquim Francisco de (2019)
Privatization, when made feasible in large numbers (as re-emerged in the Temer/MDB government, and continues in the Bolsonaro/PSL government), without consistent measures of viability, regulation and transparency, generates impacts in several spheres of life, especially labor. Privatization with set of neoliberal measures, weakens labor relationship and precarious even more labor conditions, making multidimensional psychosocial impacts and (re)shaping workers' political consciousness about resistance. In this context, trade unions stand out as organizations involved in the anti-privatization struggle, mitigating the impacts on the Labor World. Given this, the objective was to understand how the political conscience and the participation of trade unionists in collective actions against privatization in Espírito Santo (ES) during the Temer Government (2016-2018). The theoretical frame used was the Analytical Model of the Political Awareness for Understanding Participation in Collective Actions (SANDOVAL; SILVA, 2016). An exploratory methodology was used, with a qualitative methodology, applying semi-structured interviews with 10 trade unionists from different sectors who are facing the imminence of privatization in the ES. Content Analysis (BARDIN, 2006) was used to analyze interviews, by means of categories scaled in the theoretical Model. The results revealed, among other contributions: (1) to comprehend the identity dynamics of trade unionists; (2) to realize that the struggle of trade unionists against privatization goes beyond the bases, the struggle is for change also in the social sphere; (3) identify the latent and recursive interests surrounding privatization; (4) identify groups wronged by privatization; (5) to verify that trade unionists seek greater awareness and mobilization of workers and society for the effectiveness of collective action; (6) to demonstrate how the unionists' engagement in the anti-privatization movement is configured; (7) present the mobilization strategies and challenges for the construction of a consolidated anti-privatization movement in ES. Furthermore, with the support of a (inter)national literature review on the impacts of privatization in the world of work, resistance and confrontation, together with the theoretical reference, it was possible to identify three different types of political awareness of trade unionists, as well as contributions for the field of organizational studies in the field of work. It was concluded that the trade unionists have: first, a defensive political conscience, which values the defense and maintenance of labor rights; second, of a combative political conscience, contemplated by the union representatives of state-owned companies; third, of a utopian political consciousness characterized by an emancipatory vision for society and of combating social inequalities and injustices because they believe that privatization deliberately impacts fragile social groups. Finally, it was observed that the anti-privatization movement in the ES is still scattered and weakly cohesive, needing to face challenges for its future consolidation and institutionalization.